La Crónica abreviada de Don Juan Manuel, una 'lectura desviada' de la crónica alfonsí - Pablo Enrique Saracino (Medievalia)
La Crónica abreviada de Don Juan Manuel, una 'lectura desviada' de la crónica alfonsí